2010
DOI: 10.1055/s-0030-1254156
|View full text |Cite
|
Sign up to set email alerts
|

Gender Muscle Recovery During Isokinetic Exercise

Abstract: The purpose of this study was to examine the effect of two between set rest intervals (RI) on isokinetic knee extension peak torque (PT) produced by sedentary women and men. Seventeen young women (27.18 ± 4.05 yrs) and 16 young men (26.75 ± 4.73 yrs) performed 3 sets of 10 unilateral isokinetic knee extension at 60° and 180°/s. The RI between sets was 60 and 120 s, counterbalanced across 2 testing days. Statistical evaluation of the data was performed using a 3-way mixed factor ANOVA (gender x rest interval x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 39 publications
(48 reference statements)
1
17
0
Order By: Relevance
“…Further analysis revealed that strength differences between genders accounted for the majority of the performance differences observed. Previous studies have shown women have lower decrements in force output and faster recovery capacity during moderate-tohigh-intensity exercise than men (6,25). Women have been shown to have reduced ATP depletion (8), faster ATP recovery (8), lower blood lactate (12,25), lower epinephrine (12), lower respiratory exchange ratio (28), and lower glycogen breakdown in type 1 fibers (8) in response to maximal sprint and resistance exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further analysis revealed that strength differences between genders accounted for the majority of the performance differences observed. Previous studies have shown women have lower decrements in force output and faster recovery capacity during moderate-tohigh-intensity exercise than men (6,25). Women have been shown to have reduced ATP depletion (8), faster ATP recovery (8), lower blood lactate (12,25), lower epinephrine (12), lower respiratory exchange ratio (28), and lower glycogen breakdown in type 1 fibers (8) in response to maximal sprint and resistance exercise.…”
Section: Discussionmentioning
confidence: 99%
“…However, less is known regarding acute resistance exercise responses in women during RI length manipulation. Celes et al (6) showed that women recover faster than men do after 3 sets of 10 isokinetic knee extensions at 120˚$s 21 using 60-and 120-second RIs. Willardson et al (44,45) showed that during a squat protocol with 1-minute RIs, men needed a 15% reduction in load for each set in succession (to maintain repetition number), whereas women needed only a 10% reduction.…”
Section: Introductionmentioning
confidence: 99%
“…The sets and exercises were separated by a rest interval of approximately 2 minutes 16 . The elbow flexor training was performed using the free-weight bilateral biceps curl exercise with women in a standing position.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it can be presumed that the lack of adequate post-exercise recovery concerned these muscles. Many authors argue that duration of www.balticsportscience.com the rest that ensures the recovery of the exhausted muscle is individual for each human [24,25]. It was also found that reduced muscle strength is one of the symptoms of the onset of overtraining [26].…”
Section: Discussionmentioning
confidence: 99%